Changing conceptions of "mandala" in Tang China: ritual and the role of images - Wang, Michelle C. (Material religion, 2013)
"Changing Conceptions of Mandala' in Tang China: Ritual and the Role of Images" is concerned with the intersection of visionary experience with visual forms. The focus of the study is a Buddhist incantation, or Dhāranī, titled the Revered and Victorious Dhāranī of the Buddha's Usnīsa. This particular dhāranī was widely circulated in China during the Tang dynasty (618-907); for this reason, it may be approached as an important case study for studying the conceptualization of mandalas in China prior to their transmission to Japan in the early ninth century. Through a detailed examination of successive translations and ritual manuals associated with the Revered and Victorious Dhāranī of the Buddha's Usnīsa, different conceptions of mandalas and the roles that were played by images may be observed. This, in turn, responds to larger questions in East Asian Buddhism and studies of Buddhist art regarding the functions of painted mandalas during Buddhist rituals. Lastly, this article seeks to shed light on lesser-known aspects of esoteric Buddhist art in Asia, as the scholarship to date on Buddhist mandalas has primarily focused upon studies of Japanese and Himalayan works.